2020
DOI: 10.1101/2020.03.25.998138
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Establishment of a pancreatic adenocarcinoma molecular gradient (PAMG) that predicts the clinical outcome of pancreatic cancer

Abstract: BACKGROUND: A significant gap in pancreatic ductal adenocarcinoma (PDAC) patient's care is the lack of molecular parameters characterizing tumors and allowing a personalized treatment. The goal of this study was to examine whole PDAC transcriptomic profiles to define a signature that would predict aggressiveness and treatment responsiveness better than done until now. METHODS AND PATIENTS: Tumors were obtained from 76 consecutive resectable (n=40) or unresectable (n=36) tumors. PDAC were transplanted in mice t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…GemPred+ and hENT1 IHC selected independent groups of patients and had independent predictive values on both OS and DFS (Supplementary figure 6), suggesting these potentially select complementary sets of gemcitabine-sensitive patients. The GemPred+ patients were all found to be a subset of the Classical subtype [24] (Figure 5b, 92 of 389 classical, none of 72 Basal-like), supported by their distribution in the upper half of the pancreatic cancer molecular gradient [33] (Figure 5c). A multivariate analysis among patients that have received adjuvant gemcitabine in the pooled cohort showed that GemPred+ was a predictor of OS independent of clinicopathological features, the RNA levels of genes previously described to be associated with response to gemcitabine (i.e.…”
Section: Comparison and Multivariate Analysis Of Gempredmentioning
confidence: 77%
See 2 more Smart Citations
“…GemPred+ and hENT1 IHC selected independent groups of patients and had independent predictive values on both OS and DFS (Supplementary figure 6), suggesting these potentially select complementary sets of gemcitabine-sensitive patients. The GemPred+ patients were all found to be a subset of the Classical subtype [24] (Figure 5b, 92 of 389 classical, none of 72 Basal-like), supported by their distribution in the upper half of the pancreatic cancer molecular gradient [33] (Figure 5c). A multivariate analysis among patients that have received adjuvant gemcitabine in the pooled cohort showed that GemPred+ was a predictor of OS independent of clinicopathological features, the RNA levels of genes previously described to be associated with response to gemcitabine (i.e.…”
Section: Comparison and Multivariate Analysis Of Gempredmentioning
confidence: 77%
“…An important point is that the genome-wide RNA profiles in this study were obtained from routine FFPE samples with an overall low cost, supporting a wide application of the GemPred signature. Previous work has also shown that sequencing RNA from fine needle aspirates, including for metastatic patients, is feasible [33]. It should also be noted that, while the signature was developed on tumor cells, it performed well on more complex samples such as surgical specimens that have abundant stroma suggesting its relevance on diagnostic biopsies.…”
Section: J O U R N a L P R E -P R O O F Discussionmentioning
confidence: 99%
See 1 more Smart Citation